Utilização de galactomanano de sementes de algaroba (Prosopis juliflora) na elaboração de alimento lácteo congelado - Pessoa, Maria do Socorro Gomes de Pinho (2016)
The increased use of galactomannans, such as thickeners and stabilizers in the food industry, coupled with the call for functional foods with properties that participate in the control of chronic non communicable, has shown the need for more research in relation to its use in partial replacement saturated fat and improving the organoleptic characteristics: preventing or delaying a series of physical phenomena such as sedimentation of solid particles suspended in the medium, the crystallization of water or sugar, aggregation or disaggregation dispersed in food particles, such as studied here, derivative Frozen milk. The galactomannans are polysaccharides extracted from the endosperm of seeds of different species in the Fabaceae family. The objective of this work was to study an alternative and renewable source of a polysaccharide, easy access by the abundance of regional plant species and low cost. At first it was performed the extraction of galactomannan and made the microbiological analysis. Then they were performed testing the toxicity (acute and subchronic) in Swiss mice and Wistar rats respectively, at different times of treatment. We developed a derivative frozen dairy, where we use different percentages of galactomannan of the species Prosopis juliflora (0.1, 0.35, 0.6 and 0.85%) and analyzed on the rheological and sensory behavior (acceptance test with hedonic scale considering presentation, color, texture, smell, taste and attitude and consumption scales Test). The results showed a satisfactory performance of the extraction; no contamination by pathogens and no toxicity (acute and subchronic) in the analyzed parameters: biochemical, hematological, histopathological, neurological signs and behavioral. In biochemical parameters of glycemia was observed significant difference between male control rats (282 ± 18 mg glucose / dl) and rats treated with 500 mg / dl galactomannan (183 ± 5 mg / d); It was also observed a significant difference between the levels of LDLc control rats (13 ± 1mg / dl) and rats treated with 125 mg / kg galactomannan (LDLc 6 ± 1). On the results obtained, it was observed that food developed, frozen dairy derived mango flavor added to P. juliflora galactomannan presented physical, chemical, rheological and sensory favorable. So we developed a food product with ideal characteristics to be produced, safe, well accepted, with high added value, valuing a regional product and contributing to a healthier diet.